PEMANFAATAN DELAN SEBAGAI SUMBER BELAJAR PEMBELAJARAN IPA UNTUK MENDUKUNG PEMAHAMAN BIOTEKNOLOGI SISWA SMP FASE D - Fadla Fifi Amanillah; Silfia Nasifa; Dian Salsabila Larasati; Della Hariantika; Intan Miftakhuljannah; Tria Putri Agustina; Citra Tiwi Safitri; Berti Yolida; Rini Rita T Marpaung (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Science learning at the junior high school level has not widely utilized local wisdom as a learning resource, causing biotechnology concepts to be perceived as abstract. This study aimed to identify biotechnology concepts contained in Delan, a traditional shrimp paste from Lampung, and examine its potential as a science learning resource for Phase D junior high school students. The study employed a mixed-method approach with a sequential explanatory design through interviews, questionnaires, and interviews with science teachers. The results showed that Delan contains concepts related to fermentation, food preservation, raw material quality, and microbial activity. The Delan-based ethnoscience worksheet obtained a feasibility score of 90%, categorized as highly feasible. Therefore, Delan has the potential to serve as a contextual science learning resource while supporting the preservation of local wisdom.